Comparing food system sectoral changes in 2050 with historical transformations: A multi-model analysis - Gibson, Matthew; Sundiang, Marina; Mason-D’Croz, Daniel; Oliveira, Thais Diniz; Lotze-Campen, Hermann; Beier, Felicitas; Popp, Alex; van Zeist, Willem-Jan; van Meijl, Hans; de Lange, Thijs; van der Mensbrugghe, Dominique; Chepeliev, Maksym; et al. (Purdue University, 2024)
Food systems must transform in pursuit of health, sustainability, and justice goals. The scale and distribution of these profound changes across different food sectors is underexplored. We examine possible impacts on food sectors, contextualised with historical data, of a global food systems transformation by 2050. We do this through modelling a transformation scenario composed of dietary change, productivity growth, and reduction of food loss and waste using a multi-model ensemble of 8 global economic models. Preliminary results show substantial food sector restructuring, including a decline in the economic value of agricultural production (-$1.4tn) by 2050 under a transformation scenario versus current trends. Within this, the value of livestock production collapses (-$1tn) with declines also in cereal and sugar crop values of $800bn, partially offset by increases in the value of vegetable, fruit, and nut production ($700bn). Preliminary results also show changes to growth rates of agricultural land expansion from 0.56%/year on average for grazing land over the last 250 years to -0.87%/year from 2020 to 2050 in a food systems transformation scenario, compared to 0.12%/year under business-as-usual trends. The restructuring of global agriculture and food systems suggests a critical role for food policy to both catalyse such a transformation, as well as navigate the political economic consequences of its impacts.